The Effect of Work Environment and Work Discipline on Employees Performance Cijantung Office - Novingky Ferdinand; Ali Mutaufiq (International Journal of Sharia Business Management, 2022)
This study used a questionnaire as the research instrument and the sampling technique in this study used a saturated sampling technique with 32 respondents. Data was collected using multiple linear regression analysis with hypothesis testing. From the results of the study, it is known that the Work Environment and Work Discipline contribute 44.3% to the increase in Employee Performance while the remaining 55.7% is contributed by variables other than Work Environment and Work Discipline. The test results show that partially the work environment has a positive and significant effect on employee performance, partially work discipline has a positive and significant effect on employee performance, and simultaneously work environment and work discipline have a positive and significant effect on employee performance